Data analysis of local scour around abutment in compound channel - Zhang, Ruixin (Nanyang Technological University, 2020)
When building bridge structures in natural rivers, intricate local water flows, and the geological evolution of river beds will have a tremendous adverse impact on the safety of the bridge. Among the main components of the bridge, structures are abutments that are commonly placed in the floodplain of a compound channel. In a compound channel, the synergy between the main channel river channel and floodplain channel is a vital feature leading to the momentum exchange. During the flood, the water flows level exceeds the floodplain elevation. An abutment located in the floodplain would occupy some parts of water flows and cause local scour around the structures, causing an elevated risk to bridge operation. Hence, local scour around abutments is recognized as one of the most important causes of the bridge foundation’s destruction. This study mainly focuses on localized scour in proximity to bridge abutment under floodplain river status. It discussed the characteristics of the flow structure and determined the relationship between the main features and maximum clear water equilibrium scouring depth around the bridge abutments in the compound channel. Due to the high complexity of scouring hydrodynamics, existing relationships based on normal regression cannot make accurate predictions. Therefore, According to the published experimental data at home and abroad, Rationalize the data based on the ratio of abutment length to flow depth (L/yf), and two limiting cases are identified (L/yf >25 and L/yf <25). This paper established a new prediction formula of maximum abutment scours depth by dimensional analysis and multiple regression analysis using the incomplete self-similarity method. This model was built using the relative abutment length (L/yf), abutment aspect ratio (Lc/L), flow intensity (uf/uc), abutment shape factor (Ks), flow depth ratio (yf/ym), and relative sediment size (d50/ yf). Overall, comparisons of calculated and observed maximum equilibrium scour depths indicate that the formula is straightforward in composition and shows good credibility in the computation result.